2022
DOI: 10.1051/0004-6361/202243785
|View full text |Cite
|
Sign up to set email alerts
|

VLBI observations of VIK J2318−3113, a quasar atz = 6.44

Abstract: Context. The nature of jets in active galactic nuclei (AGNs) in the early Universe and their feedback to the host galaxy remains a highly topical question. Observations of the radio structure of high-redshift AGNs enabled by very long baseline interferometry (VLBI) provide indispensable input into studies of their properties and role in the galaxies’ evolution. To date, only five AGNs at redshift z > 6 have been studied with the VLBI technique. Aims. VIK J2318−3113 is a recently discovered quasar at z = 6.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
3
9
0
Order By: Relevance
“…This constrains the spectral index of the pc-scale feature to < −1.2, which is consistent with the value found for the kpc-scale radio emission [8]. These findings imply that the radio emission originates from a recently formed young quasar jet in the early Universe [19].…”
Section: Viking J23181835−3113463supporting
confidence: 89%
See 2 more Smart Citations
“…This constrains the spectral index of the pc-scale feature to < −1.2, which is consistent with the value found for the kpc-scale radio emission [8]. These findings imply that the radio emission originates from a recently formed young quasar jet in the early Universe [19].…”
Section: Viking J23181835−3113463supporting
confidence: 89%
“…The source was detected as a compact 'core' at 1.6 GHz with a flux density of 550 Jy, while no compact component brighter than 130 Jy (i.e. 5 image noise) was detected at 4.7 GHz [19]. This constrains the spectral index of the pc-scale feature to < −1.2, which is consistent with the value found for the kpc-scale radio emission [8].…”
Section: Viking J23181835−3113463supporting
confidence: 86%
See 1 more Smart Citation
“…Hovatta et al (2014) studied 190 blazar jets of the Monitoring Of Jets in Active galactic nuclei with VLBA Experiments (MOJAVE, Lister et al 2019) survey, and showed that in sources at higher redshifts e the derived core parameters are more likely contaminated by a neighbouring jet component due to the lower effective linear resolution. Interestingly, high brightness temperature values, close to the equipartition limit are rarely observed in other z > 5 blazars (Coppejans et al 2016;Zhang et al 2022), with the notable exception of J0906+6930 (An et al 2020).…”
Section: Brightness Temperaturementioning
confidence: 85%
“…However, such low brightness temperatures can also be measured in blazars due to insufficient resolution, when the core and a close jet component cannot be resolved and thus the fitted size is larger, resulting in lower T b value. Hovatta et al (2014) Interestingly, high brightness temperature values, close to the equipartition limit are rarely observed in other z > 5 blazars (Coppejans et al 2016;Zhang et al 2022), with the notable exception of J0906+6930 (An et al 2020).…”
Section: Brightness Temperaturementioning
confidence: 93%